2008
DOI: 10.1111/j.1467-6494.2007.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

What Makes A Hero? The Impact of Integrity on Admiration and Interpersonal Judgment

Abstract: Principled and expedient ideologies affect self-regulation and guide people along divergent ethical paths. A more principled ideology, indicative of higher claimed integrity, involves a greater personal commitment to ethical beliefs, standards, and self-schemas that facilitate positive social activities and help resist the temptation of illicit activities. Two studies showed that differences in reported integrity are related to people's preferences for and judgments of others. Those higher in integrity spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…Tsui (1984) found that personal reputations for performance are formed, and others have argued that reputations can form according to behaviours of fairness and integrity (e.g., Becker, 1998;Schlenker, Weigold, & Schlenker, 2008). Furthermore, performance/results and character/integrity assessments have been found to be related to trust (e.g., Kim, Ferrin, Dirks, & Cooper, 2004) and selection (e.g., Cook & Emler, 1999).…”
Section: Directions For Future Researchmentioning
confidence: 94%
“…Tsui (1984) found that personal reputations for performance are formed, and others have argued that reputations can form according to behaviours of fairness and integrity (e.g., Becker, 1998;Schlenker, Weigold, & Schlenker, 2008). Furthermore, performance/results and character/integrity assessments have been found to be related to trust (e.g., Kim, Ferrin, Dirks, & Cooper, 2004) and selection (e.g., Cook & Emler, 1999).…”
Section: Directions For Future Researchmentioning
confidence: 94%
“…While researchers like Schlenker et al (2008) defined admiration as a response toward "those who exemplify high integrity" (p. 328), Algoe and Haidt (2009) specifically defined admiration as a positive emotional "response to non-moral excellence" (p. 107). While researchers like Schlenker et al (2008) defined admiration as a response toward "those who exemplify high integrity" (p. 328), Algoe and Haidt (2009) specifically defined admiration as a positive emotional "response to non-moral excellence" (p. 107).…”
Section: Definitions Of Admirationmentioning
confidence: 99%
“…Higher integrity scores are associated with self-reported descriptions of behavior consistent with personal principles as well as beliefs that people can be more ethical in their lives (Miller and Schlenker 2007). Previous research has shown that friends can accurately identify an individual's level of integrity and that it predicts antisocial activities (lying, cheating, stealing), prosocial activities (reported helping and volunteering), and socially desirable personality/attitudinal traits (empathy, spirituality) (see Schlenker 2008;Schlenker et al 2008). Those having greater integrity are more likely to perceive questionable activities as unethical.…”
Section: Integritymentioning
confidence: 95%